2019
DOI: 10.21608/ajnsa.2019.3052.1066
|View full text |Cite
|
Sign up to set email alerts
|

New extraction technique of zirconium and hafnium from zircon mineral

Abstract: The present study is concerned primarily with optimizing the extraction of zirconium and hafnium from their naturally occurring mineral, zircon, via a wet chemical process. First, zircon is heated with molten sodium hydroxide to form zironate and silicate frit. Simple separation technique of sodium silicate from the zirconate and hafnate sodium was then applied to obtain a silicate-free frit, then the extraction of the zirconium (IV) and hafnium (IV) basic sulfates from their oxychloride solution leaving almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These spectra confirm the presence of several elements in the sample, which is in agreement with the previous reports on natural zircon samples. [ 42 ] The main elements identified include Zr, Hf, Ca, Fe, and Ce, while small amounts of Ti, Mn, Sr, Y, Th, and U. It was found that alongside the primary element zirconium (Zr) with a concentration of around 48%, ten other elements were detected in this particular sample.…”
Section: Resultsmentioning
confidence: 96%
“…These spectra confirm the presence of several elements in the sample, which is in agreement with the previous reports on natural zircon samples. [ 42 ] The main elements identified include Zr, Hf, Ca, Fe, and Ce, while small amounts of Ti, Mn, Sr, Y, Th, and U. It was found that alongside the primary element zirconium (Zr) with a concentration of around 48%, ten other elements were detected in this particular sample.…”
Section: Resultsmentioning
confidence: 96%
“…NaOH/ZrSiO4 as accordance to Equation ( 2) and (3) (Abdel-Rehim, 2005;Abdelkader, Daher & El-Kashef, 2008). The sodium silicate was leached out by the water due to its watersoluble property (Abdelkareem, 2019). This process is crucial as the hydrolysis of Na2ZrO3 can be hindered and subsequently decreasing the zirconium formation.…”
Section: It Is Clearly Shown That the Zirconium Composition Ofmentioning
confidence: 93%
“…It is a heavy mineral with excellent properties like; high hardness, high melting point, high chemical stability. This allows zircon to be utilized in important applications including; ceramics, refractory industries, foundry, abrasives, TV glass, electronics, pigments, and catalysts [1][2][3][4]. In Egypt, widespread placer deposits of black sand are intermittently distributed along the northern coast.…”
Section: Introductionmentioning
confidence: 99%